Pengaruh Motivasi Terhadap Kinerja Karyawan Pada PT. Bank Negara Indonesia (Persero) Tbk Kantor Cabang Bulukumba - Tenriana; Muh. Ilham Wardhana Haeruddin; Agung Widhi Kurniawan; Tenri Sayu Puspitaningsi Dipoatmodjo; Resky Amalia Hamka (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2024)
This research is to determine the effect of motivation on employee performance at PT. Bank Negara Indonesia (Persero) Tbk Bulukumba Branch Office. This research is quantitative research with a descriptive approach and is population research. The sample in this research was all employees of PT. Bank Negara Indonesia (Persero) Tbk Bulukumba Branch Office as many as 44 people. The hypothesis test in this research is a simple linear regression analysis test which produces the following results: Based on the results of the hypothesis test using a simple linear regression analysis test, it shows that motivation has a partial effect on performance in PT employees. Bank Negara Indonesia (Persero) Tbk, Bulukumba Branch Office.